Persebaran Meruang Forficula auricularia (Dermaptera: Forficulidae) Pada Awal Perioda Pencarian Makan - Tati Suryati Syamsudin Subahar (Institut Teknologi Bandung, 1996)
The spatial distribution of the European earwig in the early of the free foraging phase were analysed using dispersion index and spatial autocorrelation index. The observation found that during investigation period, were dominated by third instar larvae. Horizontal trapping above the ground showed that the the distribution per trap was very aggregative with dispersion index varies from 16.64 to 33.89. Spatial index of autocorrelation varies from -0.65 to 3.71, which indicate that earwigs chose certain place in their movement during this period.